A 'photorelease, catch and photorelease' strategy for bioconjugation utilizing a p-hydroxyphenacyl group. Issue 87 (14th October 2016) - Madea, D.; Slanina, T.; Klán, P.
Abstract : A bioorthogonal strategy, which combines photorelease of a strained alkyne, its cycloaddition with p -hydroxyphenacyl azide to form a 1, 2, 3-triazole adduct, and subsequent photochemical release of the triazole moiety via a photo-Favorskii rearrangement, is presented. Abstract : A bioorthogonal 'catch and photorelease' strategy, which combines alkyne–azide cycloaddition between p -hydroxyphenacyl azide and alkyne derivatives to form a 1, 2, 3-triazole adduct and subsequent photochemical release of the triazole moiety via a photo-Favorskii rearrangement, is introduced. The first step can also involve photorelease of a strained alkyne and its Cu-free click reaction with azide.